PENGEMBANGAN PLATFORM E-COMMERCE BERBASIS WEB DALAM RANGKA MENINGKATKAN DAYA SAING UMKM KABUPATEN REMBANG - Hanantyo, Burhanuddin; Sari, Nita; Farikhah, Izzah; Maulana, Reza; Maulana, Farid; Eka, Aditya (Universitas Mataram, 2024)
Complex technological advances in the current era of globalization have had an impact on various aspects of human life, one of which is the business world. Technology has created a new lifestyle for modern humans such as online shopping. This change in shopping style has a direct impact on MSMEs (Micro, Small and Medium Enterprises), which requires them to change their mindset and adapt to technological developments. MSMEs must innovate and improve to keep up with technological developments, so that the businesses they run can survive and develop for the better. Therefore, in order to help these MSMEs, Community Service and Assistance activities are carried out in the Rembang district area to help local MSMEs adapt to technological developments and develop their businesses, especially in the field of product marketing. This assistance focuses on increasing competitiveness as well as implementing E-commerce in Micro, Small and Medium Enterprises in the digital era. The methods applied are observation, interviews, analysis of existing conditions, Emergence of E-Commerce Solutions, E-Commerce Creation, E-Commerce usage assistance and evaluation. By applying some of these methods, it produces outcomes that can help MSMEs in digital marketing such as expanding market share and can increase high competitiveness so that it is hoped that sales turnover will increase.